Imposition of Criminal Sanctions on Corporations and/or Corporate Control Personnel Who Commit Money Laundering Crimes - Nurdin, Boy; Asmoro, Dwi (CV. Publikasi Indonesia, 2024)
This research purpose is to describe law enforcement arrangements for corporations and/or corporate control personnel for money laundering crimes. The author uses a normative juridical approach, using primary and secondary data. Data analysis uses qualitative analysis. In Indonesia, legal regulations regarding the prevention and eradication of money laundering crimes were initially regulated in Law Number 15 of 2002 concerning the Crime of Money Laundering (UUTPPU) which was later revised into Law Number 25 of 2003 and subsequently revoked and replaced by Law- Law Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering. The results show that perpetrators of money laundering crimes are subject to sanctions based on Articles 6, 7, 8, 9, and 10 of Law Number 8 of 2010 concerning Money Laundering Crimes. Apart from that, to anticipate the occurrence of money laundering criminal attempts in Indonesia by postponing transactions with assets suspected to originate from criminal acts. Blocking of assets known to originate from criminal acts, and Temporary suspension of transactions related to money laundering crimes.